A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages The constitution of the Council will be considered in detail with the professional and other organisations concerned. It must be primarily medical in its make-up — though not wholly so, because it will be required to express views on many questions, e.g., of hospital administration, dentistry, nursing, midwifery and pharmacy, which will involve experts other than the surgeon or physician. It is contemplated that it might consist of some thirty or forty members, representing the main medical organisations, the voluntary and publicly owned hospitals (with both medical and other representation), medical teaching and professions like dentistry, pharmacy and nursing and midwifery. The Council will be appointed by the Minister in consultation with the appropriate professional bodies, and it will select its own chairman and regulate its own procedure. The Minister will be prepared to provide the secretariat and the expenses of the Council will be met from public funds. A similar but separate body will be set up for Scotland by the Secretary of State. Local Organisation In framing their proposals for the local organisation of the new Health Service, the Government have been anxious to interfere as little as possible with the shape of representative local government. They have set out to base the new service as far as possible on the existing major local authorities, the county and county borough councils. But the requirements of the service will demand, for certain purposes, larger areas of operation or planning than the present counties and county boroughs can usually provide; for these purposes therefore it will be necessary for the counties and county boroughs to act in combination as joint authorities established over appropriate areas by the Minister, rather than in their separate capacities over their present areas. Thus, for reasons stated earlier, it is essential to its efficiency that the new hospital service shall be based, with a few exceptions, on areas larger than counties and county boroughs, and it is on this ground that the Government have proposed the establishment of joint authorities to administer that service — a proposal which still maintains for the county and county borough councils an interest in hospital administration inasmuch as they will be the constituent bodies of the new combined authority. It is clear, for reasons also given already, that the joint authority responsible for the hospital service must also be responsible for the consultant service and such clinic and other local services as need to be organised in close association with the hospitals. Preparation of local area plan One further and important duty will be placed on the new joint authorities — that of preparing a rational and effective plan for all branches of the Health Service in their area. The preparation of this plan has been referred to already in the description of the arrangements for the hospital and other individual services. But the intention is that the plan shall cover, not merely 22 36/H24/41